The Shame of Addiction - Flanagan, Owen (Frontiers in Psychiatry, 2013)
ABSTRACT: Addiction is a person level phenomenon that involves twin normative failures. A failure of normal rational effective agency or self-control with respect to the substance; and shame at both this failure, and the failure to live up to the standards for a good life that the addict himself acknowledges and aspires to. Feeling shame for addiction is not a mistake. It is part of the shape of addiction, part of the normal phenomenology of addiction, and often a source of motivation for the addict to heal. Like other recent attempts in the addiction literature to return normative concepts such as “choice” and “responsibility” to their rightful place in understanding and treating addiction, the twin normative failure model is fully compatible with investigation of genetic and neuroscientific causes of addiction. Furthermore, the model does not re-moralize addiction. There can be shame without blame.